STUDI PENDAHULUAN KADAR TIMBAL DAN KADMIUM DALAM AIR DAN IKAN NILA (Oreochromis niloticus, Linn.) SEBAGAI KAJIAN KUALITAS AIR DI BENDUNGAN TELAGA TUNJUNG, BALI - Arimardewi, Made Octiya; Restu, I Wayan; Saraswati, Suprabadevi Ayumayasari (Metamorfosa: Journal of Biological Sciences, 2018)
Telaga Tunjung Dam is located in Desa Timpag, Kerambitan, Tabanan, Bali. In its development, the area around the dam is used for agricultural and industrial activities as well as the residential which allow the presence of contaminants such as heavy metals. Based on the situation, it is necessary to do research on water quality in terms of heavy metal content, considering the dam is still utilized by the residents. This study aimed to identify the concentration of Lead (Pb) and Cadmium (Cd) in the water column and tilapia ( Oreochromis niloticus, Linn.) at Telaga Tunjung Dam, which was conducted in February 2016. The method used was purposive sampling and the sampling technique was carried out by composite of 5 stations based on the representatives of the waters of the dam. Water sampling was done 3 times every two weeks, and fish sampling was done randomly as much as 1 fish every 2 weeks. The content of heavy metals was analyzed using Plasma Atomic Emission Spectrometer ICPE-9000. Concentration of Lead (Pb) obtained in the water ranged from 0-0,009 mg/l, and Cadmium (Cd) ranged from 0,135-0,310 mg/l. In tilapia, lead concentrations were unable to be detected, and the cadmium concentration ranged from 0,330-0,728 mg/kg. The results indicate that the water in Dam Telaga Tunjung has been polluted by cadmium, because it has exceeded the standards as specified by the Regulation of Governor Bali No. 8 of 2007 about Environmental Quality Standards and Standard Criteria of Environmental Damage Class II that is equal to 0,03 mg/l, and exceeding the specified standard SNI (Indonesian National Standard) 7387:2009 of 0,1 mg/kg for fish and its products.